All Quiet on the Eastern Microelectronic Front? A Comparative Assessment of the Performance of Saxony’s Microelectronic Cluster - Leister,Tim (2019)
Following the structural transformation process in the 1990s, the government of Saxony set its hopes on the microelectronic cluster in its region to foster regional development and international competition. It is uncertain whether the cluster of Silicon Saxony has managed to meet these expectations. By comparing the cluster to four other major microelectronic clusters in Europe, the study assesses its effective performance. Supported by cluster theory and regional innovation systems, potential factors accounting for the strengths and weaknesses of the cluster are examined. The results pinpoint an ambivalence between weak innovative capacity and a strong employment effect and economic impact on the region. The weak innovative capacity is rooted in an underdeveloped private sector, the scarcity of company headquarters and the lack of R&D incentives for businesses. The strong performance of the cluster in generating employment and economic output is attributed to the manufacturing bias of the cluster and the governmental policies promoting this specialisation with regards to public R&D efforts, an industry-specific labour-pool and financial grants. Research-intense activities within the industry therefore fall short. The findings indicate that the strategy of the Saxon government so far constitutes a success. In the long term, however, challenges arise. The manufacturing bias implies difficulties to adjust to future changes once the microelectronic industry enters maturation. By giving more weight and incentives to the private sector and research- and design-intense activities, the cluster can sustain itself in the future.
Keywords: clusters; regional innovation systems; semiconductors; microelectronics; Saxony